SURVEI TINGKAT KEBUGARAN JASMANI PADA SISWA SEKOLAH DASAR - Eko Rudiansyah; Yeriko Cossato G; Robi Iza Saputra; Deki Apriyadi (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2023)
Abstract: The aim of the study was to find out how high the level of physical fitness was for the students in the high grades of Public Elementary School 03 Nanga Pinoh and Public Elementary School 28 Kelakik. The research method used is descriptive, in descriptive research is research that functions to describe or give an overview of the object under study through sample data or population as it is, without conducting analysis and conclusions that apply to the public. The results of the study were that there were 0 students or 0% in the very good classification, there were 4 students or 6% in the good classification, there were 32 students or 53% in the moderate classification, there were 24 students or 39% in the poor classification, there were 1 student or 2% in less classification. The conclusion is that the physical fitness classification of students at Public Elementary School 03 Nanga Pinoh and Public Elementary School 28 Kelakik is classified as moderate, poor, and very poor. While students who fall into the fresh or fit classification are only 4 students.Keywords: Physical, fitness Abstrak: Tujuan penelitian adalah mengetahui seberapa tinggi tingkat Kebugaran jasmani siswa kelas Tinggi SD Negeri 03 Nanga Pinoh dan SD Negeri 28 Kelakik. Metode penelitian yang digunakan adalah deskriptif, didalam penelitian deskriptif adalah penelitian yang berfungsi untuk mendeskripsikan atau memberi gambaran terhadap obyek yang diteliti melalui data sampel atau populasi sebagai mana adanya, tanpa melakukan analisis dan kesimpulan yang berlaku untuk umum. Hasil penelitian adalah Terdapat 0 siswa atau 0% dalam klasifikasi baik sekali, terdapat 4 siswa atau 6% dalam klasifikasi baik, terdapat 32 siswa atau 53% dalam klasifikasi sedang, terdapat 24 siswa atau 39% dalam klasifikasi kurang, terdapat 1 siswa atau 2% dalam klasifikasi kurang sekali. Kesimpulannya adalah klasifikasi kebugaran jasmani siswa SDN 03  Nanga Pinoh dan SDN 28 Kelakik dalam klasifikasi sedang, kurang, dan kurang sekali. Sementara siswa yang masuk dalam klasifikasi segar atau bugar hanya 4 siswa.Kata Kunci: Kebugaran, Jasmani